Implementation of Family Functions Based on Islamic Prophetic Parenting in Building Family Resilience in the Digital Era - Miftahul Jannah (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study examined the implementation of Islamic Prophetic Parenting in strengthening family functions amidst the transition from the digital 4.0 disruption era to Society 5.0. The problem addressed was the vulnerability of Indonesian families to instability, uncertainty, and permissiveness caused by rapid technological change, information overload, and emerging psychosocial risks such as parental burnout, internet gaming disorder, pornography exposure, and online infidelity. A qualitative library research approach was applied by critically reviewing national and international journals, academic books, and conference proceedings published within the past decade. Content analysis identified patterns and synthesized concepts related to family roles, religious, educational, affective, protective, social, and economic and their alignment with the principles of Prophetic Parenting, including honesty (ṣidq), responsibility (amanah), effective communication (tabligh), and wisdom (fathanah). Findings indicated that the infusion of Prophetic Parenting values reinforced moral-spiritual resilience, optimized emotional bonding, and created a cultural “filter” against harmful digital exposure. Family routines such as shared prayer, dialogue, and mutual supervision emerged as stabilizing factors mitigating overload and anxiety. The study concluded that effective family adaptation in Society 5.0 requires a dual strategy: embedding Qur’anic-prophetic values and strengthening digital literacy and self-regulation skills. These combined approaches enable families to maintain cohesion, safeguard children’s well-being, and preserve moral integrity while navigating abundant technological opportunities. Limitations of the study include the absence of empirical field data, suggesting the need for longitudinal and intervention-based research to validate causal pathways and program effectiveness.